Submucosal injection with waterjet improves endoscopic mucosal resection of colorectal adenoma – a randomised controlled clinical trial. (1st February 2017) - Belle, Sebastian; von Boscamp, Manuel; Sold, Moritz; Mack, Susanne; Pilz, Lothar; Ebert, Matthias; Kaehler, Georg
Abstract: Purpose: Endoscopic mucosal resection (EMR) of colorectal adenomas leads to a reduced incidence of, and mortality from, colorectal carcinoma. Large adenomas are especially difficult to resect. Submucosal injection is a key part of EMR, as it allows for complete resection and decreased complications. We previously demonstrated in both animal models and a clinical trial that a focussed fluid beam applied to the mucosa creates selective fluid cushions in the submucosa selective tissue elevation by pressure (STEP). In this study, we examined the potential of this new technique compared to the standard inject and cut technique. Methods: This was a monocentric prospective two armed randomised controlled clinical trial comparing the STEP technique to the standard needle injection. We included patients with Yamada I and II adenomas ≥12 mm. Results: One hundred fifty-five patients were treated in the trial. With the STEP technique there was a significantly higher rate of en-bloc resection, whereas piecemeal resection was more common in the standard arm. The odds ratio of piecemeal resection was 2.422 with a 95% confidence interval of 1.163–5.045 ( p value .0195). There was no significant difference in resection time between the two techniques, while there was a significant difference in resections speed for the STEP technique. There was also no difference in complication rates. Conclusions: This study demonstrated that the new STEP technique leads to a higher rate of en-bloc resections than the standard injection technique in endoscopic mucosa resection of colorectal adenomas. The STEP technique can play an important role in the future of EMR.